Retrospective Analysis of Look-alike and Sound-alike Drug Incidents in a Tertiary Care Hospital - Dhande, Priti P.; Mule, Akshay V.; Chaudhari, Akshay P. (Journal of Pharmacy Practice and Community Medicine)
Background: Drug names or their appearances are sometimes confusing to the healthcare professionals. These look-alike and sound-alike drugs have the risk of being wrongly used in patients leading to medication errors. Lists of such drugs are available from authorized sources to refer and implement cautions while using them for preventing harm to patients. However, there is always a chance of more possibilities of drugs which can be included in LASA category based on the different brands of drugs available in each country. Objectives: This study was planned to search out LASA drug related errors in a tertiary care hospital in Western India. Materials and Methods: Medication errors reported by Clinical Pharmacists for a duration of Feb 2017 to Feb 2020 were studied to list out LASA drugs related errors and these were then evaluated. Preventive strategies were developed to avoid similar errors in future in the study setup. Results: Out of total 1311 errors reported during the study duration of 3 years, 35 (2.67%) were LASA drug incidences. Majority of these errors were dispensing errors and of “Near miss” category 74.28% and most (24) of the errors were due to phonetically sound-alike drugs (68.57%). Dispensing errors (16) were most commonly associated with these LASA drug incidences followed by computer indenting errors (08). Conclusion: LASA drug incidences amounted to a small proportion of total medication errors but have to be considered seriously as they can be harmful to the patient if not identified on time.
Keywords: Medication errors; Look-alike; Sound-alike; Dispensing; Drug administration.